On Form, Cyclicity and Temporality in Leoš Janáček’s String Quartet No. 1 - Mohammad, Iyad A. (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aimed is to identify the underlying temporal structures, procedures and devices employed by Janáček in the composition of his First-String Quartet, by way of a thorough analysis of musical forms, relations and cyclicities of recurring themes and motifs, and an examination of referential semantic structures. Methods: The study applied a descriptive-analytical method in the framework of a textual approach to the composition under consideration. This includes identifying procedures of contrast, juxtaposition, interpolation, temporal intercutting, and superimposition described by T. Clifton, often employed together with a montage-style technique. Results: The results of the study of our analysis clearly show Janáčeck’s preference for the palindrome arch form and rondo-like forms, combined with features of ternarity. In their recurrences themes are mostly varied, occasionally transposed, and often curtailed, sometimes to the duration of a mere referential reminder. This form entails a specific temporality related in the palindrome form to a retrograde temporal directionality. The superimposition of themes and accompaniment textures also entails a superimposition of their temporal strata. Another poignant feature of this quartet’s temporality is the use of referential-semantic devices. This includes the multiplicity of inter-sectional and inter-movement citations of themes, motifs, and intonations. Conclusions: In the light of the results, the study recommends further empirical experimental research of the perception of temporal categories outlined in this paper, and to explore the relation of semantic referential structures and elements of speech in the melodic of Janáček.